Normative data for accommodative facility and vergence facility in a sample of African school children aged 8–17 years - Darko-Takyi, Charles; Manu, Ebenezer; Yirrah, Victoria; Owusu, Sandra; Boakye, Kumi Owusu; Abraham, Carl Halladay; Osei, Kwame Okyere (Frontiers in Neuroscience, 2026)
Background/objectivesThe existing literature on normative data for accommodative facility (AF) in African populations is limited to high school students. There is no normative data for vergence facility (VF) in African children, so there are no benchmarks for comparison in case analysis, diagnosis, and management. The study aimed to establish normative data for AF in children aged 8–12 years. Additionally, the study sought to determine normative data for VF in children aged 8–17 years in the Cape Coast metropolis, Ghana.MethodsNormal children (510) were recruited through a comprehensive oculo-visual examination of 2,300 basic school-going children, aged 8–17 years. AF was measured with a ± 2D flipper lens for 1 min. VF was measured with a 3-base-in/12 base-out flipper prism for 1 min. Normative data were derived using the median with interquartile ranges (IQR) and considering the spread of data within the minimum and maximum ranges.ResultsA median value of 13 cpm with IQR of 4 cpm was determined for monocular accommodative facility (MAF). The normative central tendency for MAF for school children 8–17 years ranges from 9 to 17 cpm; data were widely spread, with a minimum of 4 and a maximum of 20 cpm. A median value of 13 cpm with IQR of 3 cpm was determined for the binocular accommodative facility (BAF). The normative central tendency for BAF for school children aged 8–17 years ranged from 9 to 14 cpm; data were widely spread, with a minimum of 5 and a maximum of 20 cpm. A median value of 14 cpm with IQR of 4 cpm was determined for VF. The normative central tendency for VF for school children 8–17 years ranged from 10 to 18 cpm; data were widely spread, with a minimum of 6 and a maximum of 21 cpm.ConclusionThe normative data apply only to similarly aged Ghanaian children and serve as standards for comparison to clinical data for MAF, BAF, and VF during case analysis.